CDIO Initiative: A Guarantee for Successful Accreditation of Engineering Programmes - Abdulkareem Sh. Mahdi Al-Obaidi (Universitas Pendidikan Indonesia, 2021)
The accreditation bodies and engineering councils set a number of qualifying requirements and accreditation criteria to ensure the quality of engineering graduates and programmes. One of these requirements is the engineering curriculum. Some institutions using the traditional engineering curriculum often face difficulties and burden to meet the accreditation minimum academic requirements as their curriculum lacks the innovation and the integration of graduate attributes such as personal, interpersonal, teamwork, entrepreneurship, development of life skills and emotional wellbeing, among many. This eventually leads to deferred or even declined accreditation. To overcome these difficulties, the CDIO initiative is an ideal tool for successful accreditation. The CDIO standards, syllabus, engineering curriculum, and learning outcomes are not only meeting what accreditation bodies require, but they offer innovative curriculum more on high-level cognitive skills set in the context of the product-system lifecycle; Conceiving-Designing-Operating-Implementing metaphases. This paper shares a successful engineering education experience of the School of Engineering/Taylor’s University and how the CDIO initiative contributed not only to a successful accreditation but also to have a new innovative engineering curriculum. The adopted new curriculum is innovative, hands-on and project-based in order to achieve integrated learning where acquiring discipline-specific knowledge and CDIO skills take place simultaneously